Fatty acid desaturase 2 affects the milk‐production traits in Chinese Holsteins. (15th March 2022) - Fu, Yihan; Jia, Ruike; Xu, Lingna; Su, Dingran; Li, Yanhua; Liu, Lin; Ma, Zhu; Sun, Dongxiao; Han, Bo
Abstract: As a member of the fatty acid desaturase family, fatty acid desaturase 2 ( FADS2 ) gene is a rate‐limiting enzyme in the synthesis of unsaturated fatty acids and within/near to the reported QTL regions for milk‐production traits. We previously found that FADS2 is differentially expressed during different lactations of Chinese Holstein cows, and participates in lipid metabolic processes by influencing the insulin, PI3K‐Akt, MAPK, AMPK, mTOR and PPAR signaling pathways. Therefore, we considered this gene as a candidate gene for milk‐production traits. In this study, we identified 12 SNPs in FADS2 by re‐sequencing, including two SNPs in the 5′ flanking region, one in the seventh exon, five in introns, two in the 3′ untranslated region and two in the 3′ flanking region. The 29:g.40378819C>T is a missense mutation that causes alanine (GCG) to be replaced with valine (GTG). Through single marker association analysis, we found that all of the 12 SNPs were significantly associated with 305 day milk yield, fat yield, fat percentage, protein yield or protein percentage ( p  < 0.0493). The results of the subsequent haplotype association analysis also confirmed the associations between the gene and milk‐production traits. In summary, this study suggests that there is a significant genetic association between FADS2 and milk‐production traits, and that the SNPs with significant genetic effects can provide important molecular information for the development of a genomic selection chip in dairy cattle.